Hybrid Nanowires: Vertically Aligned Hybrid Core/Shell Semiconductor Nanowires for Photonics Applications (Adv. Funct. Mater. 48/2013). (23rd December 2013) - Macias‐Montero, Manuel; Filippin, A. Nicolas; Saghi, Zineb; Aparicio, Francisco J.; Barranco, Angel; Espinos, Juan P.; Frutos, Fabian; Gonzalez‐Elipe, Agustin R.; Borras, Ana
<x xml:space="preserve">Abstract</x> Single‐crystal organic nanowires are fabricated and covered by an inorganic wide‐bandgap semiconducting shell via chemical vapor deposition. The wires are vertically aligned by A. Borras and co‐workers and supported on processable substrates. This method is widely applicable to a range of materials. The waveguide effect on the fluorescence emission of the organic cores and their application as nanoscale waveguides in the 550–750 nm range are explored on page 5981 using perylene and ZnO. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>